Integration of Creative Da'wah Training, Digital Literacy, and Community Counseling as a Model for Preventing Religious Hoaxes among Teenagers on Social Media - Abdul Karim; Agung Obianto; Indifatul Anikoh (CENDEKIA: Jurnal Pengabdian Masyarakat, 2026)
The spread of religious hoaxes on social media poses a serious challenge for Indonesian youth, whose digital literacy levels are still moderate. This Community Service (PkM) activity aims to improve digital literacy, creative da'wah content production skills, and critical awareness among youth through community counseling. Held in Tegalsari Village, Banyuwangi, East Java (January-March 2026) with 27 participants aged 15-20, the activity used a community empowerment-based Participatory Action Research (PAR) approach. Results showed an increase in the average digital literacy score from 52.4 to 78.9, with the highest increase in the information verification indicator (+35.8 points). Participants produced 54 digital da'wah content, 92.6% of which were deemed suitable for dissemination without revision. Ninety-six percent of participants stated that the activity was very beneficial, and 100% wanted the program to continue. These findings confirm that the integration of digital literacy, creative da'wah, and community counseling is effective in developing critical and responsible digital da'wah agents.